Quantitative Assessment Of The Effectiveness Of Drip Irrigation Kits In Alleviating Food Shortages And Its Success In Zimbabwe: A Case Study Of Gweru And Bikita Districts - Mugabe, Francis T.; Chivizhe, Joseph; Hungwe, Chipo (Food Agriculture, Natural Resources Policy Analysis Network, 2020)
About 23,000 drip kits were distributed in 53 districts of Zimbabwe by 20 Non Governmental Organizations with the assistance of LEAD Zimbabwe and USAID/OFDA between 2003 and 2006. The program’s objective was to mitigate the food shortage crisis in Zimbabwe by helping families grow their own vegetables and earn extra income.